Gadolinium-doped polymeric as a shielding material for X-ray - S. M., Tajudin; A. H., Aminordin Sabri; M. Z., Abdul Aziz; F., Tabbakh (2021)
A relatively new polymeric base compounds (CnH2n) had been proposed as a shielding material for 150 keV photon for an X-ray laboratory. When doped with 8 % gadolinium (Gd), a thickness of 2 cm shielding compound (6 g cm-3 ) could attenuate more than 90 % of the incident photons with an average dose rate reduction of more than 88 % for 150 keV incident photon. While considering the transmitted photons after the shielding, it is necessary to account for reflected photons and its dose contribution. The reflected photons and ambient dose equivalent were calculated for single-photon energy of 150 keV and an X-ray of 150 kVp. The shielding compound was successfully attenuated most of the incident photon energies particularly below 90 keV. In both cases of photon sources, two significant reflected photon peaks at ~40 and 50 keV were observed as a result of Gd characteristic X-rays. A Compton scattered photon at energy of 95 keV appeared as a result of large scattering angle within 130o -140o for 150 keV incident photons. Thus it is necessary to add a thin inner layer at the source-facing side of the shielding compound to shield the radiation workers and patient inside the X-ray room during the X-ray procedure. An iron layer with thickness of 0.5 cm was adequate to shield almost completely the reflected photons and ambient dose for X-ray 150 kVp source.